Design considerations and modeling of fiber reinforced 3D printed parts. (1st March 2019) - van de Werken, Nekoda; Hurley, Joel; Khanbolouki, Pouria; Sarvestani, Ali N.; Tamijani, Ali Y.; Tehrani, Mehran
Abstract: 3D printing of high strength, lightweight, and relatively inexpensive parts can save engineers time and resources not possible otherwise. Continuous fiber reinforced polymer 3D printing has recently emerged to address this need. In contrast to conventional composites that consist of unidirectional or woven laminates, continuous fibers in 3D printed composites can be used to only partially reinforce each layer and/or be printed in curved patterns (infill patterns) to enhance mechanical performance. Understanding the mechanics of this new class of 3D printed (additively manufactured) composites is required for their optimal design and utilization in various applications. In this work, the thermo-mechanical response and failure mechanics of 3D printed composites are evaluated and correlated to their structure. We show that the strength of the 3D printed specimens depends strongly on the infill pattern and part geometry. Specifically, fiber curvatures and interfaces between reinforced and non-reinforced regions result in stress concentrations, multi-axial stress states, and pre-mature failure in parts. To better understand the failure in 3D printed composite structures, finite element analysis (FEA) was used. To this end, anisotropic properties were assigned to each element of the generated mesh based on the local fiber direction. FEA was able to capture experimental failure stresses and shed light on the failure mechanisms in tested specimens. Finally, we present rudimentary design rules that can be useful for designing 3D printed fiber reinforced parts.